PROJECT BASED LEARNING (PjBL) BERBASIS INSENTIF UNTUK MATAKULIAH KOMPUTER AKUNTANSI - Komalasari, Sanda Patrisia (Ensiklopedia of Journal, 2024)
The study aims to develop a learning program for the Computerized Accounting Practicum course. This research was conducted among second-semester Diploma in Accounting students in Class A3 of the Faculty of Economics and Business at Andalas University during the even semester of the 2022/2023 academic year. The inherent learning system of this course is fundamentally based on practicum. To enhance learning outcomes and other benefits, we introduced a project element into this learning system. This project involves a community service program. Students are required to find a school to serve as the object of their service. The activities they can undertake include the socialization and training of computerized accounting usage, which they have learned during the practicum class. They then report these activities in the form of a service article. Articles that have been published and meet the incentive submission requirements will be proposed for incentives to the university through the supervising lecturer. From the assessment of learning outcomes and the results of questionnaires distributed to students and the community benefiting from this learning, we found a positive contribution. The implemented learning activities have been able to enhance students' understanding of the course material. This activity will improve the students' ability for independent learning, their interest in the course, as well as their teamwork and communication skills.Keywords: Computerized Accounting Practicum, Project-Based Learning, Incentive